Characterization of Affective Behaviors and Motor Functions in Mice With a Striatal-Specific Deletion of Bmal1 and Per2 - Schoettner, Konrad; Alonso, Mariana; Button, Margo; Goldfarb, Cassandra; Herrera, Juliana; Quteishat, Nour; Meyer, Christiane; Bergdahl, Andreas; Amir, Shimon (Frontiers in Physiology, 2022)
The expression of circadian clock genes, either centrally or in the periphery, has been shown to play an integral role in the control of behavior. Brain region-specific downregulation of clock genes revealed behavioral phenotypes associated with neuropsychiatric disorders and neurodegenerative disease. The specific function of the clock genes as well as the underlying mechanism that contribute to the observed phenotypes, however, are not yet fully understood. We assessed anxiety- and depressive-like behavior and motor functions in male and female mice with a conditional ablation of Bmal1 or Per2 from medium spiny neurons (MSNs) of the striatum as well as mice lacking one copy of Gpr88. Whereas the conditional knockout of Bmal1 and Per2 had mild effects on affective behaviors, a pronounced effect on motor functions was found in Bmal1 knockout mice. Subsequent investigation revealed an attenuated response of Bmal1 knockout mice to dopamine receptor type 1 agonist treatment, independently of the expression of targets of the dopamine signaling pathway or mitochondrial respiration in MSNs. The study thus suggests a potential interaction of Bmal1 within the direct dopamine signaling pathway, which may provide the link to a shared, MSN-dependent mechanism regulating affective behavior and motor function in mice.